Hubungan Menyusui dan Pola Makan dengan Kanker di RSUD AW Sjahranie Samarinda - Rini Ernawati (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2021)
Non contagious disease which is the main cause of death now is cancer. The most common cancer types are breast, lung, colon, rectum, stomach and liver cancer. Breast cancer is the main cause of death in women due to cancer, while lung cancer is the leading cause of death in men. Some of the risk factors for cancer are breastfeeding, diet, age, genetics, smoking and alcohol. The purpose of this study was to analyze the relationship between breastfeeding and diet towards cancer in RSUD AW Sjahranie Samarinda. The number of respondents was 125 who were chosen with purposive sampling. The instrument used was questionnaire. Chi square test were used with a significance level of 95% (α = 0.05). The results of this study indicate that the following variables includes; breastfeeding has a p value of = 0.000, and diet with a value of p = 0.003. This shows that breastfeeding and dietary factors has a correlation with the type of cancer. It is necessary to improve health through counseling on the importance of breastfeeding for up to 2 years for mothers who have babies and everyone should consume healthy food every day. Keywords: breastfeeding , diet, cancer